Proteomic Analysis of the Air-Way Fluid in Lung Cancer. Detection of Periostin in Bronchoalveolar Lavage (BAL) - Zhou, Yangying; Yang, Weiming; Ao, Minghui; Höti, Naseruddin; Gabrielson, Edward; Chan, Daniel W.; Zhang, Hui; Li, Qing Kay (Frontiers in Oncology, 2020)
Background: Bronchoalveolar lavage (BAL) is a specific type of air-way fluid. It is a commonly used clinical specimen for the diagnosis of benign diseases and cancers of the lung. Although previous studies have identified several disease-associated proteins in the BAL, the potential utility of BAL in lung cancer is still not well studied. Based upon the fact that the majority of secreted proteins are glycoproteins, we have profiled N-glycoproteins in BAL collected from lung cancers, and investigated the expression of glycoproteins such as the matrix N-glycoprotein, periostin, in lung cancers. Methods: BAL specimens (n=16) were collected from lung cancer patients, and analyzed using mass spectrometry-based quantitative N-glycoproteomic technique. Additional BAL specimens (n=39) were independently collected to further evaluate the expression of periostin by using an enzyme-linked immunosorbent assay (ELISA). Results: A total of 462 glycoproteins were identified in BAL samples using N-glycoproteomic technique, including 290 in lung adenocarcinoma (ADC, n=5), 376 in squamous cell carcinoma (SQCC, n=4), 309 in small cell lung carcinoma (SCLC, n=4) and 316 in benign lung disease (n=3). The expressions of several glycoproteins were elevated, including 8 in ADC, 12 in SQCC and 17 in SCLC, compared to benign BALs. The expression of periostin was detected in all subtypes of lung cancers. To further investigate the expression of periostin, an ELISA assay was performed using additional independently collected BALs (n=39) The normalized levels of periostin in benign disease, ADC, SQCC and SCLC were 255 ± 104 (mean ± SE) and 4002 ± 2181, 3496 ±1765 and 1772 ± 1119 ng/mg of total BAL proteins. Conclusion: Our findings demonstrate that proteomic analysis of BAL can be used for the study of cancer-associated extracellular proteins in air-way fluid from lung cancer patients.